2007
DOI: 10.1186/1479-5876-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of cutaneous wound healing

Abstract: Background: Although the sequence of events leading to wound repair has been described at the cellular and, to a limited extent, at the protein level this process has yet to be fully elucidated. Genome wide transcriptional analysis tools promise to further define the global picture of this complex progression of events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(88 citation statements)
references
References 29 publications
5
83
0
Order By: Relevance
“…The macrophage population present immediately following tissue injury possesses predominantly M1 characteristics [20, 21]. Transition to an M2 phenotype occurs concurrently with resolution of the inflammatory process and the initiation of the remodeling phase of wound healing [20].…”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The macrophage population present immediately following tissue injury possesses predominantly M1 characteristics [20, 21]. Transition to an M2 phenotype occurs concurrently with resolution of the inflammatory process and the initiation of the remodeling phase of wound healing [20].…”
Section: 0 Introductionmentioning
confidence: 99%
“…Transition to an M2 phenotype occurs concurrently with resolution of the inflammatory process and the initiation of the remodeling phase of wound healing [20]. This process represents the default mammalian host response to tissue injury, and generally results in the formation of localized scar tissue.…”
Section: 0 Introductionmentioning
confidence: 99%
“…A comprehensive genetic study mapping the gene expression profiles during the cutaneous wound healing has motivated the development of gene delivery strategies in facilitating wound healing (Deonarine et al, 2007). Biomaterial-based nucleic acid delivery systems reduce degradation, enhance uptake, and control the treatment dose.…”
Section: Biomaterial-based Wound Therapiesmentioning
confidence: 99%
“…If the genetic contribution to proper palatogenesis is unquestionable, and the list of genes involved in cleft lip and palate established at about 300 (Jugessur et al, 2009), it has been challenging to generate a workable list of genes involved in wound healing, mainly because of the complexity of the process and the difficulties of obtaining relevant human samples. Nevertheless, a few studies have performed gene expression profiling of cutaneous wound healing (Deonarine et al, 2007; Roupe et al, 2010; Nuutila et al, 2012), or identified a genetic signature unique to non-healing wounds (Charles et al, 2008), yet none provided access to the full list of differentially-regulated genes. Using available information from these studies, we estimated the percentage of reported wound-healing genes that shared a role in CL/P.…”
Section: When Things Go Wrongmentioning
confidence: 99%